A q-Analog of the Hua Equations - Bershtein, O.; Sinel’shchikov, S. (Журнал математичної фізики, аналізу, геометрії, 2009)
A necessary condition is established for a function to be in the image of a quantum Poisson integral operator associated to the Shilov boundary of the quantum matrix ball. A quantum analogue of the Hua equations is introduced. Mathematics Subject Classification: 81R50, 17B37, 31B10.